Studies of peach gum polysaccharide on gut microbiota in vitro fermentation by human feces - Bing Xu; Ping Sun; Jun Lu; Yi Wang; Xianrui Lin; Chenfei Chen; Jianxi Zhu; Huijuan Jia; Xinwei Wang; Jiansheng Shen; Chuang Yu; Tao Feng (Journal of Future Foods, 2025)
Peach gum polysaccharides have multiple biological functions, such as anti-oxidation, blood lipids reduction, and immune protection. However, their impact on the gut microbiota was still unclear. Here, high throughput sequencing was used to study the regulatory effects of peach gum polysaccharide on gut microbiota using an in vitro fermentation model of human gut microbiota. The results showed that gut microbiota species increased significantly and α-diversity index (Sobs, Ace, Chao1, Shannon) decreased significantly after polysaccharide fermentation compared with control group (distilled water). At phylum level, the relative abundance of Firmicutes and Actinomyces increased (61.76% vs. 56.64%, 28.24% vs. 23.11%). In contrast, relative abundance of Bacteroides decreased significantly (8.10% vs. 19.21%). At genus level, the relative abundance of Bifidobacteria, Colinella and Parazobacteria increased significantly (21.43% vs. 19.08%, 6.32% vs. 3.73%, 6.37% vs. 0.00%), while the relative abundance of Bacteroides and Prevotella decreased significantly (3.83% vs. 5.52%, 3.49% vs. 12.15%). Precisely, peach gum polysaccharide can effectively regulate the structure of gut microbiota and has potential probiotic effects including anti-obesity, anti-inflammatory, maintenance of gut epithelial barrier and so on.